Metodologi dan Karakteristik Penafsiran dalam Tafsir Al-Kashshaf - Muhammad Solahudin (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2016)
Tafsīr al-Kashshāf, is a tafsīr written by a Muslim scholar who support ahl al-'adl wa al-tawḥīd or known as Mu'tazilah. This tafsīr is influenced by power relations, the terms referred to Michel Foucault, that served ideological interests. This articles employs analytical descriptive to investigate the doctrines of Mu'tazilah that influenced al-Zamakhsharī in his methodological interpretation of tafsīr al-Kashshāf . The result of this study shows that the doctrines of Mu'tazilah influenced al-Zamakhshari’s interpretation of the Qur’anic verses accommodating to the opinion of the Hanafi School and the theology of Mu'tazilah. He tried to confine understanding of verses by changing their meanings in accordance with the five creeds of Mu’tazilah as follows: al-tawḥīd, al-‘adl, al-wa’d wa al-wa’īd, al-manzilat bayna al-manzilatain, and al-‘amr bī al-ma’rūf wa al-nahy ‘an al-munkar. On the other side, tafsīr al-Kashshāf employed tahlīlī method and bi al-ra'y model of interpretation. Tafsīr al-Kashshāf utilized critical reasoning in its interpretation, employed the principles of freedom, applied Arabic grammatical (naḥwu), provided qirā’ah-qirā’ah, and showed the beauty of literary and language styles of the Qur’an.